5.3k views
12 votes
2x-3(2x-3)+2=45 pls solve fully

User Rbrown
by
4.9k points

2 Answers

3 votes

Answer:


x=(-4)/(33)

Explanation:

Let's start with simplifying the equation. To do this, let's simplify the parenthesis. We can use the distributive property to simplify the parenthesis. We now have


2x-6x+9+3=45

Next, we can start adding. We can add 2x and 6x, and 9 and 3.


-4x+12=45

Now that we've simplified the equation, we can start solving the equation. First, let's subtract 12 from each side.


-4x=33

The last thing that we need to do is divide -4 from each side.


x=(-4)/(33)

User Miasbeck
by
4.8k points
12 votes

Answer:x=-17/2

Explanation:

User Dcpartners
by
5.3k points